Natural fibres for geotextiles - Leao, A. L. [UNESP]; Cherian, B. M. [UNESP]; Souza, S. F. de [UNESP]; Kozlowski, R. M.; Thomas, S.; Kottaisamy, M. (Woodhead Publ Ltd, 2012)
Natural fibre-based geotextiles can compete with polymeric geotextiles on both technical and economic grounds. However, to increase their competitiveness, new areas of application must be developed, with the biggest market share concentrated in three fibres: jute, coir and sisal. Although jute and coir geotextile products are currently available worldwide, mainly in India, sisal fibre geotextiles have yet to be developed. Sisal is particularly promising due to its mechanical properties and large and consistent supply. Natural fibres like hemp, kenaf and African palm are also suitable raw materials for geotextiles.
Keywords: geotextiles; natural fibre; woven; nonwoven; geomembranes; geogrids; geocomposites